Of smart phones and Facebook: Social media`s changing legal landscape provides cautionary tales of "Pinterest" for sport organizations - Larkin, B.; McKelvey, S. (Journal of Legal Aspects of Sport, 2015)
Due to the prevalence with which today`s consumers access and utilize social media, sport organizations are increasingly devoting more financial and personnel resources to marketing through these platforms, and are seemingly getting a return on their investment. The benefits of using social media platforms must, however, be mitigated by the hurdles that can arise from careless and potentially unlawful usage. As evidenced by our discussion of recent social media lawsuits, administrative decisions by federal regulators, and the rules and regulations governing promotions and contests, we show that potential legal troubles can be mitigated through the thoughtful crafting of internal social media policies as well as continued monitoring of social media platform policies.